Diagnostik Holistik Dan Penatalaksanaan Komprehensif Ibu Hamil Pada Pasien Ny. N 30 Tahun Dengan Kehamilan Risiko Tinggi Kek Dan Anemia Di Puskesmas Bangetayu Semarang - Fatuh Rohman; Ratnawati Ratnawatia; Aris Maulan (CV. Jasa Sukses Abadi, 2026)
High-risk pregnancy due to chronic energy deficiency (CED) and anemia remains a significant concern in primary healthcare because of its association with adverse maternal and neonatal outcomes. This case report describes a 30-year-old pregnant woman at 28 weeks of gestation diagnosed with CED (mid-upper arm circumference 22.5 cm) and iron deficiency anemia (hemoglobin 10.1 g/dL) at Bangetayu Community Health Center, Semarang. A holistic diagnostic approach was applied, integrating medical assessment with family function evaluation (Family APGAR and SCREEM), nutritional behavior analysis, and environmental factors. Management included iron and folic acid supplementation, provision of fortified supplementary food, intensive nutrition counseling, and structured family and community involvement. The distinguishing aspect of this case lies in the integration of clinical management with systematic family and environmental assessment to address multifactorial risk determinants. The expected clinical outcomes were improvement in maternal nutritional status, optimized weight gain during pregnancy, prevention of low birth weight and stunting, and reduced risk of perinatal complications. This case highlights that comprehensive, family-centered, and community-oriented interventions are essential in strengthening early detection and management of high-risk pregnancies in primary care settings.